Explainable AI: Identification of Writing from Famous Figures in Indonesia Using BERT and Naive Bayes Methods - Firdaus Putra Kurniyanto; Agus Hartoyo (Universitas Budi Darma, 2023)
Identifying the writings of well-known figures in Indonesia is a form of appreciation for the writing itself. By knowing the language style used by every famous figure in Indonesia, we can know the uniqueness of each writer, and it can help us understand the thoughts, ideas, and ideas they convey. This research has yet to be done, so it is still interesting to do further research. In this study, only a few writers were used, so it is still impossible to know the overall language style used by every famous figure in Indonesia. In this study, a system was built to determine the language style used by well-known figures in Indonesia based on their writing using the BERT, Naïve Bayes, and LIME algorithms for explainable AI processes. The results are that the BERT algorithm is better at classifying text with an accuracy of 92% compared to Naïve Bayes, which has an accuracy of 90%. From this study, it was also found that KH. Abdurrahman Wahid and Emha Ainun Nadjib have almost the same style of language in which their writings contain many words with political and religious elements. Dahlan Iskan, his writing contains many words with political and socio-cultural elements, while Pramoedya Ananta Toer's writing uses many pronouns.